2022
DOI: 10.1002/oby.23387
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and diet in populations with obesity: Role of the Na+/K+‐ATPase transporter signaling in severe COVID‐19

Abstract: Objective The triad of obesity, a high‐protein diet from animal sources, and disturbed gut microbiota have been linked to poor clinical outcomes in patients with COVID‐19. In this report, the effect of oxidative stress resulting from the Na+/K+‐ATPase transporter signaling cascade is explored as a driver of this poor clinical outcome. Methods Protein–protein interactions with the SARS‐CoV‐2 proteome were identified from the interactome data for Na+/K+‐transporting ATPase subunit α‐1 (ATP1A1), epidermal growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Some genes that were identified over the serum and plasma patient data are involved in the cellular response to DNA damage and repair, namely, RAD51 recombinase (RAD51), mediator of DNA damage checkpoint 1 (MDC1), bloom syndrome RecQ-like helicase (BLM), and Erb-B2 receptor tyrosine kinase 2 (ERBB2). ERBB2, belonging to the epidermal growth factor receptor family of receptor tyrosine kinases, had also been previously linked to the cytokine release storm and thus severity of an infection with SARS-CoV-2 ( Khitan et al, 2022 ). This gene was especially of interest in combination with obesity and gut microbiome in COVID-19 patients ( Khitan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some genes that were identified over the serum and plasma patient data are involved in the cellular response to DNA damage and repair, namely, RAD51 recombinase (RAD51), mediator of DNA damage checkpoint 1 (MDC1), bloom syndrome RecQ-like helicase (BLM), and Erb-B2 receptor tyrosine kinase 2 (ERBB2). ERBB2, belonging to the epidermal growth factor receptor family of receptor tyrosine kinases, had also been previously linked to the cytokine release storm and thus severity of an infection with SARS-CoV-2 ( Khitan et al, 2022 ). This gene was especially of interest in combination with obesity and gut microbiome in COVID-19 patients ( Khitan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…ERBB2, belonging to the epidermal growth factor receptor family of receptor tyrosine kinases, had also been previously linked to the cytokine release storm and thus severity of an infection with SARS-CoV-2 ( Khitan et al, 2022 ). This gene was especially of interest in combination with obesity and gut microbiome in COVID-19 patients ( Khitan et al, 2022 ). Finally, we explored the tissue context of COVID-19–associated genes, identified in blood of mostly severe patients, independently if they were additionally associated to the genetic predisposition.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity is a risk factor for poor outcomes of COVID-19. Using bioinformatics, Khitan et al found that oxidative stress due to deregulated Na + /K + -ATPase transporter signaling could lead to increased risk for more severe forms of the disease in obese individuals [ 50 ].…”
Section: The Role Of Oxidative Stress In Covid-19 Pathogenesismentioning
confidence: 99%